STUDI KARAKTERISTIK STOMATA BEBERAPA JENIS TANAMAN REVEGETASI DI LAHAN PASCAPENAMBANGAN TIMAH DI BANGKA - Lina Juairiah (Widyariset, 2014)
Study on stomatal characteristics of some reclamation plants in the post tin-mining land in Bangka was conducted based on Wholemount method. According to the classification of stomata density, Trema orientalis, Commersonia bartramia, and Syzygium garcinifolium were belong to high density category (> 500/mm2), while stomatal density V. pinnata was in the category of medium density (300-500/mm2). The average length of stomata T. orientalis, V. pinnata, and S. garcinifolium include length size (20-25 µm) criteria, while C. bartramia include long enough size (< 20 µm). Based on characteristics that the four types of stomata plants show V. pinnata grown more adaptive of post tin -mining land in Bangka compared with T.orientalis,C. bartramia, and S. garcinifolium.